El derecho a la vida de usuarios del transporte público y comercial. - Santórum Chamba, Karla Noemí (2024)
This paper analyzes the right to life in relation to the new decision of the Constitutional Court of Ecuador regarding the elimination of the custodial penalty for the use of slick tires. This has led to a heated debate on the effectiveness of sanctions in road safety. Therefore, using interviews with legal experts and surveys of the general population, the research reveals an ambivalent perception towards this reform. Thus, the results indicate a generalized concern about the possible decrease in drivers' awareness of tire maintenance, while recognizing the need for more preventive and educational approaches to road safety as an element that the Court aspires citizens to possess. The study contextualizes Ecuador's decision within international trends, contrasting it with successful strategies in other countries and considering the unique challenges of the Latin American context, such as corruption and lack of trust in authorities. It concludes that while there is an openness to alternative methods of promoting road safety, there is a critical need to complement the elimination of custodial sentencing with comprehensive education programs and effective enforcement mechanisms. This research contributes to the dialogue on how to effectively balance law enforcement, road safety education and citizen responsibility in the specific context of Ecuadorian society, offering recommendations for a more effective road safety policy adapted to local realities.